Attempts of Central Asian Scholars to Prove Euclid's Fifth Postulate - Z.Sh. Kupaysinova (Genius Journals, 2022)
The article presents the work of Central Asian scientists who tried to prove the V postulate of Euclid.
Keywords: Fifth postulate; constant quantity; parallel straight lines